(3GdMGTjI GdShOGAs - (3GdcGTj Ch GdcGTGfj, jMji Hf CMeO, J HYO (B745 (3g`s ((3CMeO Hf eMeOs)
(3ChdgG (B:s
(3HSe Gddg bhdg GdefI YdjfG Sdc WQjb GdYed HGdMOjK eYfi dCf MbjbI GdMeO YfO GdeMbbjf GXgGQ GdUaGJ GdceGdjI Ohf Gdbhd GdeNUhUI dG jbGd cja jUHM GdKfGA HeG gh ePehe YbdG s
(3BNQgG (B:s
(3dh HbjJ GddebOeI UGObI Ydi gPG GGdJbOjQ hgh Chd GdcdGe Ke Edi ef YfO GdLhGH jTJed Ydi eRjO JaVjd dG jdjb PcQg HcJGH dG jMJed RjGOI JWhjd Je GdcJGHs
(3JHUQI GdYfhGf (B:s
(3MGTjI Ydi BOGH GdHMK ddSeQbfOjs
(3JHUQI GdeDda (B:s
(3aj Chdg bGd (B:(3CHh efUhQ eMeO Hf GdaJM GdeYQha H (B( (3QJGL GdSYjO (B) (3, hGdeDda eKHJ ceG aj cTa GdXfhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\135s
Keywords: (3GdadSaI hGdefWbs